FEEDBACK CONTROL OF DC MOTORS WITH LONG RANGE HC 12 TRANSCEIVER AND ARDUINO - TODICA, M. (Studia Universitatis Babeș-Bolyai Physica, 2019)
The work demonstrates the possibility to control DC motors at long distance with feedback. The system uses the radio transceivers HC 12, Arduino board and LCD keypad shield. Complete description of the hardware and software parts of the system is presented.